2016
DOI: 10.1136/acupmed-2015-010950
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for Fibromyalgia in Primary Care: A Randomised Controlled Trial

Abstract: Objectives To evaluate the efficacy of an individualised acupuncture protocol for patients with fibromyalgia. Methods Randomised controlled multicentre trial, blinded to participants and to data analysts. Conducted in three primary care centres in southern Spain. A total of 164 participants aged over 17 years and diagnosed with fibromyalgia were enrolled in this trial; 153 participants completed the study. Participants were randomly assigned to either the real intervention (individualised acupuncture, IA) or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(91 citation statements)
references
References 35 publications
(24 reference statements)
1
80
0
Order By: Relevance
“…Taking into consideration OTP performed on-site, prescribed in the MCPC, acupuncture was the most frequently prescribed. Some evidence supports acupuncture effectiveness for chronic low back pain treatment [ 41 ], fibromyalgia [ 42 ], and neck pain treatment [ 43 ]. It is increasingly prescribed [ 40 ], but the lack of strong studies that clearly prove its effectiveness has delayed its global recognition [ 44 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Taking into consideration OTP performed on-site, prescribed in the MCPC, acupuncture was the most frequently prescribed. Some evidence supports acupuncture effectiveness for chronic low back pain treatment [ 41 ], fibromyalgia [ 42 ], and neck pain treatment [ 43 ]. It is increasingly prescribed [ 40 ], but the lack of strong studies that clearly prove its effectiveness has delayed its global recognition [ 44 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Integrative modalities (sometimes referred to as complementary and alternative medicine) that have been described as effective in the management of pediatric pain include hypnosis, yoga, acupuncture, and massage [99,100,101,102,103,104,105,106,107]. Active mind-body techniques, such as guided imagery, hypnosis, biofeedback, yoga, and distraction each and all evoke pain modulation by engaging a number of mechanisms within the analgesic neuraxis.…”
Section: Interdisciplinary Rehabilitative Pediatric Pain Program: mentioning
confidence: 99%
“…This is true not only in Taiwan, because patients with fibromyalgia also receive acupuncture in the other countries, such as Germany [ 20 ]. Previous studies in the United States, Spain, and Iran have demonstrated the efficacy of acupuncture in fibromyalgia [ 21 23 ].…”
Section: Discussionmentioning
confidence: 99%